Diversity of insect carried-fungi in chili (Capsicum annuum) crop at Banyumas District, Central Java Province, Indonesia - AGUS SUROTO; ENDANG MUGIASTUTI; TARJOKO TARJOKO; EKA OKTAVIANI; MUHAMMAD BAHRUDIN (Society for Indonesian Biodiversity, 2023)
Abstract. Suroto A, Mugiastuti E, Tarjoko, Oktaviani E, Bahrudin M. 2023. Diversity of insect carried-fungi in chili (Capsicum annuum) crop at Banyumas District, Central Java Province, Indonesia. Biodiversitas 24: 3394-3406. This study aimed to determine the species of fungal pathogens that have the potency to be carried by various insects in endemic areas of chili (Capsicum annuum L.) disease and locations with high populations of chili insect vectors in the Banyumas District. The insect samples were collected from three chili planting locations in Banyumas District (Karanglewas, Sumbang, and Sokaraja Sub-districts) from March to November 2022. The following methods carried out the research: (i) determining the sampling location, (ii) insect sampling and identification, (iii) isolation and purification of fungal pathogen carried by insects, (iv) pathogenicity test, (v) identification of fungal pathogens based on morphology characters. The exploration of 13 villages in 3 (three) sub-districts of Banyumas District found 60 insects collected from healthy and diseased chili plants. Totally, six genera of fungi were isolated and identified, namely Fusarium, Pythium, Curvularia, Penicillium, Geotrichum, and Phytophthora. This is preliminary research on the interaction between plants, microbes, and insects. Understanding these aspects is essential, not only from an ecological perspective but also for improving the genetic quality of crops as well as for integrated pest management.